An Assessment of Coping Mechanism for Reducing Unemployment Syndrome among Graduates in Nigeria: Array - Babatunde, Bayode Olusanya; Oyero Kazeem, Bayo Liafeez; Fetuga, Omoshalewa Maryam (Acta Universitatis Danubius. Œconomica, 2021)
Abstract: This study was conducted to access the impact of coping mechanism on unemployment syndrome reduction among the graduate youths in Osun state, Nigeria. Survey method was used in this study and purposive sampling technique was adopted to collect data through administration of questionnaire. Two set of groups were involved. Four hundred and seven copies of questionnaire were administered on graduate benefiaries of N power in Osun State and 60 copies of questionnaire were also administered on the supervisors in each of the 30 local government areas of Osun State. (2 per local government). Linear Regression analysis was used to achieve the formulated hypotheses and objectives. The findings showed that Hypothesis 1 R2= 0.620, sig= 0.000, p < 0.05), for Hypothesis 2 (R2=0.455, sig =0.000, p < 0.05). The study established that individual commitment, self assiduous, focus and goal oriented are keen to self sustainability in this current situation in Nigeria today. The study concluded that individual determination (individual commitment, Focus, goal oriented and self assiduous) as coping mechanisms have significant impact on unemployment syndrome reduction among graduates in Osun State. Therefore, the study recommended that government should intervene and practically involve in the activities of the beneficiaries of any fund release to reduce unemployment in this era of ongoing COVID 19 pandemic in Nigeria to reduce economic wastage of fund.